ANALYZING THE TPACK OF SCIENCE TEACHER BASED EXPERIENCE FOR TEACHING GLOBAL WARMING IN SECONDARY LEVEL - Yanti, Meili; Riandi, Riandi; Suhandi, A (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
Technological pedagogical and content knowledge (TPACK) has been one of the steering frameworks that widely employed by researchers in order to examine and develop teachers' knowledge of integrating technology into instruction. This thing also viewed as a modern signature pedagogy within science teachers education integration of technology with science area content and effective pedagogy. In this article the author purposes to describe TPACK of science teachers using a new contextualized TPACK model with global warming. The participants were science teachers from three districts in Indonesia and have different ages from 24 until 34 years old. They were completed questionnaire to measure their ability to sync content, pedagogy, and technology in global warming material. Content Representation was applied to support quantitative data. Our results reveal that the teachers have different knowledge of TPACK. The implications of this study are that experienced teachers perceived higher barriers in integrating technology in classrooms than less experienced teachers.